2013
DOI: 10.3390/md11072574
|View full text |Cite
|
Sign up to set email alerts
|

APS8, a Polymeric Alkylpyridinium Salt Blocks α7 nAChR and Induces Apoptosis in Non-Small Cell Lung Carcinoma

Abstract: Naturally occurring 3-alkylpyridinium polymers (poly-APS) from the marine sponge Reniera sarai, consisting of monomers containing polar pyridinium and nonpolar alkyl chain moieties, have been demonstrated to exert a wide range of biological activities, including a selective cytotoxicity against non-small cell lung cancer (NSCLC) cells. APS8, an analog of poly-APS with defined alkyl chain length and molecular size, non-competitively inhibits α7 nicotinic acetylcholine receptors (nAChRs) at nanomolar concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 52 publications
1
50
1
Order By: Relevance
“…Based on this information, α7nAChRs antagonists were revealed to attenuate the proliferative effects of nicotine in lung cancer (22). An analog of 3-alkylpyridinium polymers with a defined alkyl chain length and molecular size (APS8) may inhibit tumor may inhibit tumor growth and trigger the intrinsic apoptotic pathways in NSCLCs (55). Another study has confirmed that α7nAChRs antagonists including d-tubocurarine and α-cobratoxin (α-CbT) may reduce tumor cell growth factors stimulated by Table I.…”
Section: Function and Mechanisms Of α7nachr On Cell Proliferationmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on this information, α7nAChRs antagonists were revealed to attenuate the proliferative effects of nicotine in lung cancer (22). An analog of 3-alkylpyridinium polymers with a defined alkyl chain length and molecular size (APS8) may inhibit tumor may inhibit tumor growth and trigger the intrinsic apoptotic pathways in NSCLCs (55). Another study has confirmed that α7nAChRs antagonists including d-tubocurarine and α-cobratoxin (α-CbT) may reduce tumor cell growth factors stimulated by Table I.…”
Section: Function and Mechanisms Of α7nachr On Cell Proliferationmentioning
confidence: 97%
“…Nicotine may also induce NSCLC cells invasion, migration and mesenchymal transition, which were mediated by α7nAChR involving the MEK/ERK signaling pathway (27). Meanwhile, the effects induced by nicotine may be suppressed by pharmacological intervention using α7nAChR selective antagonists or by genetic intervention using α7nAChR small interfering RNAs (55,68). α-bungarotoxin appeared to be one of the specific inhibitor for α7nAChR, which blocked metastatic tumors by NNK-induced tyrosine phosphorylation of proto-oncogene tyrosine-protein kinase Src, protein kinase Cι and focal adhesion kinase (65).…”
Section: Function and Mechanisms Of α7nachr On Metastasismentioning
confidence: 99%
“…α-Cobratoxin, a high-affinity α7-nAChR antagonist reduced tumor growth in nude mice orthotopically engrafted with NSCLC cells [59]. An α7nAChR inhibitor (APS8) may suppress NSCLCs proliferative effects of nicotine [58]. These studies revealed that nicotine/α7nAChR signals mediate proliferation in lung cancer.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…α7nAChR levels in patients with SCC who are active smokers are correlated with their smoking history [31]. The function of α7nAChR-mediated lung cancer progression including in proliferation [31,[54][55][56][57][58][59][60][61][62][63][64][65], angiogenesis [66], and metastasis [39,[67][68][69], has been revealed (Fig. 2).…”
Section: The Potential Mechanisms Of Nicotine On Lung Cancer Progressionmentioning
confidence: 99%
“…Our overall results are in line with studies investigating the cytotoxicity of nicotine in various in vitro systems. Nicotine, at a concentration of 1μM, was shown to exert a minor effect on the viability of MRC-5 normal fibroblasts, while the proliferation of both human lung cancer cell lines A549 and SKMES-1 (13% for A549 and 14% for SKMES-1) was slightly enhanced (22). The treatment of MRC-5 cells with nicotine-free tobacco extract (1 mg/mL, but no 0.1 mg/mL) reduced (p < 0.05) the viability of MRC-5 cells by 42%, indicating that components other than nicotine in tobacco leaves exhibited cytotoxic effect (23).…”
mentioning
confidence: 96%